Parental risk factors for congenital diaphragmatic hernia: a large German case-control study - Schulz, Felicitas; Jenetzky, Ekkehart; Zwink, Nadine; Bendixen, Charlotte; Kipfmüller, Florian; Rafat, Neysan; Heydweiller, Andreas; Wessel, Lucas; Reutter, Heiko; Müller, Andreas; Schaible, Thomas (BMC pediatrics, 2021)
Evidence for periconceptional or prenatal environmental risk factors for the development of congenital diaphragmatic hernia (CDH) is still scarce. Here, in a case-control study we investigated potential environmental risk factors in 199 CDH patients compared to 597 healthy control newborns.